WANTED: Peacebuilders, not Troublemakers in the U.S.-China Relations in an Era of Global Challenges - Douglas de Castro (Ukrainian Policymaker, 2023)
This study explores the complex structure of current international relations, highlighting the significant influence of fear and perception on the global political situation, specifically in connection to the U.S.-China dynamic. The research examines how the prevailing atmosphere in this setting is characterized by an abundance of fear and misunderstandings, which in turn prompt governments to adopt defensive and aggressive tactics in order to safeguard their interests, which frequently result in heightened disputes and security predicaments. The analysis focuses on the intricate interactions between the United States and China, which are two of the most prominent global powers. Their profound economic reliance, along with their ideological differences, requires a comprehensive comprehension of their relationship. This is particularly relevant in talks over the proposed foreign pollution fee introduced by U.S. Senator Bill Cassidy. It provides an illustrative example of how environmental, economic, and geopolitical factors interact. The study advocates for the significance of collaborative strategies in global policy formulation, particularly in the aftermath of the post-pandemic era, highlighting the importance of policies that recognize the interdependence in global problems and the overlapping areas of international systems, while also taking into account historical and persistent global disparities.